Long‐term impact of childhood selective dorsal rhizotomy on pain, fatigue, and function: a case–control study. (15th June 2017) - Daunter, Alecia K; Kratz, Anna L; Hurvitz, Edward A
Abstract : Aim: Selective dorsal rhizotomy (SDR) is a surgical treatment for spasticity in children with cerebral palsy (CP). Studies suggest long‐lasting effects of SDR on spasticity; long‐term effects on symptoms and function are not clear. This study tested whether adults with CP (average 22y after SDR) report less pain, fatigue, and functional decline than a retrospectively assessed non‐surgical comparison group. Method: This was a case–control study. Eighty‐eight adults with CP (mean age 27y; SDR=38 male/female/missing=20/16/2; non‐surgical [comparison]=50, male/female=19/31) recruited from a tertiary care center and the community completed a battery of self‐reported outcome measures. Regression models were used to test whether SDR status predicted pain, fatigue, functional change, and hours of assistance (controlling for Gross Motor Function Classification System level). Results: SDR status did not significantly predict pain interference ( p =0.965), pain intensity ( p =0.512), or fatigue ( p =0.404). SDR related to lower decline in gross motor functioning ( p =0.010) and approximately 6 fewer hours of daily assistance than for those in the comparison group ( p =0.001). Interpretation: Adults with CP who had SDR in childhood reported less gross motor decline and fewer daily assistance needs than non‐surgically treated peers, suggesting the functional impact of SDR persists long after surgery. What this paper adds: After selective dorsal rhizotomy, adults report decreased motor decline and need for care, controlling for Gross Motor Function Classification System level. They also reported higher function. They have similar prevalence of pain and fatigue as peers. Pain and fatigue are prevalent in both groups, emphasizing the need to address other causes of these complaints in addition to spasticity. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.